2017
DOI: 10.3892/mco.2017.1534
|View full text |Cite
|
Sign up to set email alerts
|

Traditional and cumulative meta‑analysis: Chemoradiotherapy followed by surgery versus surgery alone for resectable esophageal carcinoma

Abstract: Abstract. The role of neoadjuvant chemoradiotherapy followed by surgery (CRTS) compared with surgery alone (SA) for resectable esophageal carcinoma has been established by several randomized controlled trials (RCTs). The present study aimed to investigate the difference in survival between the two treatments by a review of meta-analyses. Related research indicators were extracted from RCTs investigating CRTS or SA for resectable esophageal carcinoma by searching electronic databases for eligible articles. Outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…For the most prevalent chronic diseases including hypertension, diabetes, COPD, coronary heart disease, cerebrovascular disease, and cancer, we conducted the cumulative meta-analysis according to the season of admission of the patients and the increasing sample size of the included studies within each season. A cumulative meta-analysis is helpful to assess the dynamics of how the summary results change with a newly added study ( 26 ). R 4.0.3 (The R Foundation for Statistical Computing, Vienna, Austria) was used to conduct a cumulative meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
“…For the most prevalent chronic diseases including hypertension, diabetes, COPD, coronary heart disease, cerebrovascular disease, and cancer, we conducted the cumulative meta-analysis according to the season of admission of the patients and the increasing sample size of the included studies within each season. A cumulative meta-analysis is helpful to assess the dynamics of how the summary results change with a newly added study ( 26 ). R 4.0.3 (The R Foundation for Statistical Computing, Vienna, Austria) was used to conduct a cumulative meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
“…A recent meta-analysis of 22 randomized trials also reported improved survival with neoadjuvant therapy versus esophagectomy alone for patients with locally advanced esophageal cancer, but more for adenocarcinoma than squamous-cell carcinoma. 33 However, response to neoadjuvant therapy is unpredictable and low—29% in CROSS—and survival of complete responders is worse than that of patients undergoing esophagectomy for early-stage cancers, the hysteresis effect of down-staging. 5…”
Section: Discussionmentioning
confidence: 99%
“…25 A cumulative meta-analysis can be performed multiple times; not only can it obtain summary results and provide a comparison of the dynamic results, but also it can assess the impact of newly added studies on the overall conclusions. 26 For example, initial observational studies and systematic reviews and meta-analyses suggested that frozen embryo transfer was better for mothers and babies; however, recent primary studies have begun to challenge these conclusions. 27 Maheshwari et al 27 therefore conducted a cumulative meta-analysis Following the basic meta-analysis principles to analyze the incidences of adverse events of studies to investigate whether these conclusions have remained consistent over time and found that the decreased risks of harmful outcomes associated with pregnancies conceived from frozen embryos have been consistent in terms of direction and magnitude of effect over several years, with an increasing precision around the point estimates.…”
Section: Cumulative Meta-analysismentioning
confidence: 99%